The responsibility of the maritime agent in Iraqi legislation: A comparative study - أمين خالص نافع; ناصر رحيم راهي (Journal of Legal Sciences, 2019)
The study of civil liability is one of the most important issues of interest in all jurisprudential, judicial and legislative direction, because of the problems and difficulties it requires. the solution requires a focused effort that sets its source, basis, scope, and control with extreme care and accuracy to achieve the right and enable the injured party to obtain fair compensation both with scope of the contractual or tort liability. In fact, the contract of the maritime agency is what is called the comparative jurisprudence (the contract of the ship’s agency) connecting between the terminals of the maritime carrier on the on hand and the maritime agent on the other hand. It is the source of responsibility of each party to the other. The most important thing that a maritime agency contract is the responsibility of the agent is concentrated in carrying out the legal acts and related to the name of the carrier and for his account in order to implement the contract of maritime transport concluded between the carrier in the field of transporting objects or passengers in the field of transport of persons and may be damaged by mistakes or mistakes which entails the search for another type of responsibility towards them, which is the to liability.